2005
DOI: 10.1021/jp0506484
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Pathways in the Interactions of Reactive Metal Atoms with Organic Surfaces:  Vapor Deposition of Ca and Ti on a Methoxy-Terminated Alkanethiolate Monolayer on Au

Abstract: In situ time-of-flight secondary ion mass spectrometry, infrared spectroscopy, and X-ray photoelectron spectroscopy measurements have been used to characterize the interfacial chemistry that occurs upon physical vapor deposition of Ti and Ca atoms onto a -OCH(3) terminated alkanethiolate self-assembled monolayer (SAM) on Au{111}. While the final result for both metals is near-exhaustive degradation of the methoxy terminal group and partial degradation of the alkyl chains to inorganic products such as carbides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 57 publications
3
76
0
Order By: Relevance
“…Conventional metal deposition techniques such as evaporation, sputtering, and chemical vapor deposition bring considerable energy to the surface during the deposition process and are known to damage the surface molecular layer 271,272 and result in metalorganic interfaces with inconsistent, inhomogeneous, and leaky electrical conducting properties. 273,274 To minimize the impact of the metallization process, "soft" techniques, such as indirect deposition, [275][276][277] nano-particles deposition, [278][279][280] electrochemical methods, [281][282][283] "lift-off float-on (LOFO)," 284,285 mercury droplet contacts, 286,287 micro-contact printing, [288][289][290][291] have been specially designed and implemented to achieve more consistent results. The effect of a molecular layer on the SBH is found to be less consistent and predictable than its effect on the surface potential of the semiconductor or the metal.…”
Section: Dv¼mentioning
confidence: 99%
“…Conventional metal deposition techniques such as evaporation, sputtering, and chemical vapor deposition bring considerable energy to the surface during the deposition process and are known to damage the surface molecular layer 271,272 and result in metalorganic interfaces with inconsistent, inhomogeneous, and leaky electrical conducting properties. 273,274 To minimize the impact of the metallization process, "soft" techniques, such as indirect deposition, [275][276][277] nano-particles deposition, [278][279][280] electrochemical methods, [281][282][283] "lift-off float-on (LOFO)," 284,285 mercury droplet contacts, 286,287 micro-contact printing, [288][289][290][291] have been specially designed and implemented to achieve more consistent results. The effect of a molecular layer on the SBH is found to be less consistent and predictable than its effect on the surface potential of the semiconductor or the metal.…”
Section: Dv¼mentioning
confidence: 99%
“…[10,75] Interactions between end groups of the molecular layer and deposited metals have also been reported for Cu on porphyrin monolayers [84,147] and on SAMs. [130,[148][149][150][151] Notably, particular end-group/top contact metal combinations can yield a chemical association that reduces metal penetration into the monolayer. [150,151] An FTIR study of aromatic monolayers bonded to Si via SiÀC bonds derived from diazonium reduction reported that soft deposition of 100 nm of Au produced minor perturbations of the IR spectrum, while direct e-beam deposition of the same thickness caused serious degradation of the aromatic structure of the monolayer.…”
Section: Progress Reportmentioning
confidence: 99%
“…Notable examples include assessment of structural changes in the molecular layer accompanying metal deposition [75,77,84,130,149,152] and in situ spectroscopy of finished [76,152] and functional [74,85,175] molecular junctions. While these experiments are far from simple, an analogy from chemistry illustrates their importance.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Studies made for the series of ÀCH 3 , ÀOH, ÀCOOH, ÀCOOCH 3 , and -CN reveal extensive reactions and the penetration depth of Ti into the SAM molecular backbone appears to correlate somewhat with the oxygen component of the terminal group following the series ÀCH 3 < ÀOH < ÀCOOCH 3 < ÀCOOH [23,35]. In the case of the ÀOCH 3 group, it has been reported that Ti deposition results in parallel reactions with both the ÀOCH 3 terminus and ÀCH 2 À backbone groups to degrade the SAM extensively [33,56]. Extensive degradation to form carbides also has been observed for aromatic SAMs [33,40,41].…”
Section: Timentioning
confidence: 95%
“…For the alkaline earth metals this effect can be useful for generating low work function cathode metal electrodes in organic light emission diodes (OLEDs) and organic electro luminescence display (OELDs). Alkaline earth metals, however, are not only active in injecting electrons into conjugated molecules but also are chemically reactive and can form reaction products with many organic groups [56,57]. In general, the alkali metals are not used for commercial applications but are useful to study for their simple behavior as one electron injection atoms.…”
Section: Timentioning
confidence: 99%